(3CKQ hSGFd hCLgRI GdJOQjH GdMOjKI aj JfejI GdESJQLGY (B: (3OQGSI JLQjHjI Ydi HYV QjGVjj chfZ ah hhThs - (3HheOjf, WGQbs; (3HhQfGf TQja, eUWais; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3gOaI GdOQGSI Edi GdJYQa Ydi GdOhQ GdaYGd GdPj JdYHg cd ef hSGFd hCLgRI GdJOQjH GdMOjKI hGdeJeKdI aj (B((3bfGY GdJOQjH, GdJOdjc, GdCTYI ahb GdHfaSLjI, SGYGJ JMOjO GdehGbY (B"GPS"(3, GdhNR HGdEHQ GdUjfjI, Se GdfMd(B) (3Ydi GdGSJTaGA, hCj gPg GdhSGFd CcKQ aYGdjI aj JfejI GdGSJTaGA dOi GdQjGVjjf NdGd aJQI GdefGaSGJ(B. (3GTJedJ GdOQGSI Ydi YjfI GNJjQJ HGdWQjbI GdYeOjI echfI ef KeGfjI (B(08) (3QjGVjjf eY bjGS bHdj hHYOj daQjb fLe UGdM HGj HhdGjI SWja ddQjGVGJ GdbJGdjI aj JNUU GdchfZ ah hhTh deOI ehSejf eJJGdjjf, eY JWHjb cd hSjdI ef hSGFd GdGSJTaGA deOI CQHYI (B(08) (3CSGHjY cGedI hJWHjb cdj ddhSGFd aj XQa (B(48) (3KeGfjI hCQHYhf CSHhY, GfJgjL GdefgL GdJLQjHj dedGFeJg eY WHjYI YfhGf GdOQGSI, MjK bGe GdHGMK HbjGS fHV GdbdH hcPdc bjGS VZW GdOe GdEfbHGVj hGdEfHSGWj, Ke JWHjb GNJHGQ (B"(3Qhaj(B" (3GdPj jSJOd Hg Ydi caGAI GdGSJQLGY, Ke HYO Pdc GNJHGQ (B(VAMEVAL) (3deOI GKfJj YTQ (B(12) (3ObjbI abW dCf GdgOa ef GdGNJHGQ LeY GdeYdheGJ GdNGUI HbjGS cd ef JQcjR MeV GddHf aj GdOe, bjGS JQcjR ScQ GdOe, bjGS fSHI fbd GdOe ddCcSLjf, JeJ GdeYGdLI GdEMUGFjI Yf WQjb MSGH GNJHGQ J SJjhOfJ, hJMdjd GdJHGjf GdeJYOO (B(ANOVA)(3, HGSJYeGd CTgQ HQGeL GdQRe GdEMUGFjI ddYdhe GdEfSGfjI hGdELJeGYjI (B(SPSS 26)(3, CXgQJ fJGFL GdOQGSI Cf GdhSGFd GdCcKQ JCKjQG HGdJQJjH gj Se GdfMd, GdCTYI ahb GdHfaSLjI, GdhNR HGdEHQ GdUjfjI, hcPdc YOe GdGNJdGa Hjf gPg GdhSGFd GdeSJYedI HOQLI cHjQI, MjK jJhLH Ydi GdeOQHjf hVY HQGeL NGUI HhSGFd GdGSJTaGA Vef GdHQGeL GdJOQjHjI ChdG, hGdMaGX Ydi GddjGbI GdHOfjI ddQjGVjjf KGfjG(B. (3GdcdeGJ GdOGdI(B: (3GSJTaGA, GSJQLGY, hSGFd GdGSJTaGA, bfGY GdJOQjH, GdJOdjc, CTYI ahb HfaSLjI, SGYGJ JMOjO GdehGbY (B(GPS)(3,hNR HGdEHQ GdUjfjI, Se GdfMd(B. (3edNU GdHMK HGddZI GdEfLdjRjI(B: The study aimed to identify the effective role played by each of the modern training methods and devices (training mask, massage, ultraviolet rays, GPS watches, Chinese acupuncture, bee venom) on recovery, and which of these methods is more effective in Developing the recovery of athletes during the competition period. s
(3GdOcJhQGgs
Keywords: (3GdJOQjH GdQjGUj GdfNHhjs; (3chfY ah hhThs; (3hSGFd GdGSJQLGYs